Barriers to long‐acting injectable atypical antipsychotic use in Japan: Insights from a comparative psychiatrist survey - Yoshiyo Oguchi; Nobumi Miyake; Kumiko Ando (Neuropsychopharmacology Reports, 2024)
Abstract Aims To investigate the negative attitudes of Japanese psychiatrists toward atypical long‐acting injectable (LAI) antipsychotics, which are the current mainstream LAIs in Japan. Methods We surveyed 69 Japanese psychiatrists using a 5‐point Likert scale to assess their attitudes toward atypical LAI antipsychotics. Our assessment referenced concerns identified in a study conducted in Japan a decade ago, which found significant differences when compared with a survey of German psychiatrists. We also identified the factors influencing these negative attitudes. Additionally, the results were compared with those of previous Japanese and German studies. Results More than 50% of Japanese psychiatrists expressed negative attitudes toward atypical LAI antipsychotics in various areas. These concerns included apprehensions about cost, reluctance to recommend them initially, pain from injections, complexity of switching to LAI, usage in first‐episode cases, and sufficient medication adherence with oral drugs. In all three studies, cost and adequate adherence to oral medication were concerns that exceeded the average of the three negative comments. Age and experience in psychiatry influenced the psychiatrists' attitudes toward using these drugs in first‐episode cases. Conclusions These findings shed light on the reasons for the underutilization of atypical LAI antipsychotics and suggest opportunities to enhance their appropriate use in clinical settings.